A Panorama of the Urological Diseases at the Former Military Teaching Hospital of Cotonou - SOSSA, JEAN; FANOU, LIONELLE; Hounto, Yao Félicien; Yevi, Dodji Magloire Inès; Hodonou, Fred Jean-Martin; AVAKOUDJO, JOSUÉ DEJINNIN GEORGES (My University, 2023)
Background: Urological care has been advancing quickly over the last ten years in Benin. In order to conveniently support that trend towards better urological care standards, decision-makers need sound data on urological diseases in the country. Objective: To determine the prevalence of urological diseases in the former Military Teaching Hospital of Cotonou. Patients and Method: We retrospectively collected the urological diseases that the institution had managed from January 2012 to December 2020. We used Excel© 2010 and SPSS© to analyze the collected data. Results: 4244 patients, i.e. 3717 males (87.58%) and 527 females (12.42%) were managed during the study period. The main diseases diagnosed were benign prostatic hyperplasia (32.61%, n = 1384), erectile dysfunction (10.44%, n = 443), chronic prostatitis (5.94%, n = 252), prostate cancer (4.03%, n = 171), and ejaculatory disorders (3.44%, n = 146). In patients ≤ 15 years, predominant diseases were peritoneal vaginal canal (15.9%, n = 43), circumcision (15.6%, n = 42), testicular dystopia (10.7%, n = 29), hydrocele (7.8%, n = 21), and hypospadias (5.6%, n = 15). Wilms tumor (1.9%, n = 5) was the first cancer, testicular (0.4%, n = 1) and para-testicular (0.4%, n = 1) tumors were the next. In patients > 15 and ≤40 years, the main diseases were infertility (14.1%, n = 189), chronic prostatitis (12.9%, n = 173), erectile dysfunction (10.1%, n = 135), ejaculatory disorders (6.2%, n = 83), genital infections (6.2%, n = 83) and urinary stone (4.9%, n = 66). The first cancer was kidney cancer (0.97%, n = 13) followed by bladder cancer (0.3%, n = 4) and testicular tumor (0.3%, n = 4). In patients >40 years, the most prevalent diseases were BPH (52.0%, n = 1370), erectile dysfunction (11.7%, n = 308), prostate cancer (6.5%, n = 171), inguinal hernia (5.1%, n = 134), and urinary stone (3.9%, n = 102). Prostate cancer is the first cancer; the next were bladder (0.95%, n = 25) and kidney (0.68%, n = 18) cancers. Conclusion: Benign prostatic hyperplasia and urological cancers (prostate, bladder
Keywords: Urological Diseases; Former Military Teaching Hospital of Cotonou